ECG self-study book - Wang, K. (Jaypee Brothers Medical Publishers, 2014)
ECG Self-Study Book is a practical guide to help trainees interpret ECGs and recognise cardiac abnormalities. Divided into thirty sections, each part describes twelve cases illustrating a related set of abnormalities seen in different heart diseases, along with their interpretation. The book presents 400 practice ECG tracings, with explanations and diagnoses for reference. Key features of each tracing, logic behind the ECG findings and their clinical relevance are emphasised to help understanding. Many cases include multiple choice questions or require trainees to draw a ladder diagram for practice.